Domain classification and analysis of national institutes of health‐funded medical physics research. Issue 2 (7th January 2021) - Scarpelli, Matthew; Whelan, Brendan; Farahani, Keyvan
Abstract : Purpose: The American Association of Physicists in Medicine (AAPM) previously developed a research database consisting of the National Institutes of Health (NIH) grants that were awarded to its members. The purpose of this report is to classify these NIH grants into various medical physics subdisciplines and analyze the scope of AAPM member research. Methods: For this report, an algorithm classified grant topics into medical physics research subdisciplines (grants from 2002 to 2019 were analyzed). This algorithm utilized a search for common words and phrases within grant titles, keywords, abstracts, and activity codes to perform the classification. AAPM member grants were compared with non‐AAPM member grants in various relevant subcategories to assess what percentage of these grants was held by AAPM members. Results: The percentage of AAPM member grants that included words relating to both imaging and therapy (image‐guided therapy grants) increased from 13% (27/207) in 2002 to 27% (79/293) in 2019. The percentage of AAPM member grants utilizing words relating to artificial intelligence increased from 8% in 2002 to 20% in 2019. From 2002 to 2019, AAPM member grants referenced cancer more than all other diseases combined. The majority of AAPM member grants included words relating to clinical research (81% of grants in 2002 and 99% in 2019). When comparing AAPM member with non‐AAPM member grants it was found that in 2019 AAPM members held a substantial fraction of all NIH grants that referenced stereotactic radiation therapies (41%), radionuclide therapies (10%), brachytherapies (35%), intensity‐modulated radiation therapies (45%), and external beam particle therapies (55%). From 2002 to 2019, the percentage of AAPM membership holding NIH grants decreased for males (3.2% down to 2.3%) and increased for females (0.8% up to 1.3%) Conclusions: The majority of grants awarded to AAPM members focus on clinical research, which underlies the translational aspect of medical physics and suggests medical physicists are uniquely positioned to help translate new technologies such as artificial intelligence into the clinic. Since 2002, NIH grants awarded to AAPM members have increasingly referenced some form of image‐guided therapy, suggesting opportunities for continued innovation of imaging technologies. A substantial fraction of all radiotherapy‐related research grants were awarded to AAPM members, emphasizing the important role physicists have in developing radiotherapy‐related treatments.